Granger Test and ARDL Model for the Socio-Economic Challenges Investigation: Public Expenditure Components, Economic Growth, and Inflation - Fatma Zohra Hamadouche; Bekhta Hamadouche; Malak Mohammad Ghandour; Aicha Hamadouche; Brahim Boutrig (SocioEconomic Challenges)
This study investigates the relationship between inflation recurrent expenditure, capital expenditure, and economic growth in Algeria in 1980–2022, employing Granger causality and an ARDL model. The results obtained confirm the hypothesis on the existence of a cointegration relationship between public expenditure components, economic growth, and inflation; the long-term results show that recurrent expenditure has a positive and significant relationship with inflation — a 1% increase in current expenditures leads to a 2.14% increase in inflation. Furthermore, capital expenditure negatively and significantly impacts inflation (at a 10% significance level); an increase of 1% in capital expenditure leads to an approximately 1.08% decrease in the inflation rate. GDP per capita also hurts the inflation rate in the long term (at a 10% significance level). An increase of 1% in GDP per capita leads to a 2.94% decrease in the inflation rate. The exchange rate has a negative and significant impact on inflation; any increase in the exchange rate by 1% leads to a reduction in inflation by 1.31%. In the short term, capital expenditure is the only variable with a significant relationship with inflation, where a 1% increase drives inflation up by 1.08% in the same year and 1.13% in the next. The error correction term (-0.75) highlights a strong adjustment mechanism, with deviations from long-term equilibrium corrected within approximately 16 months. The causality test results suggest unidirectional causality from economic growth to inflation at the 5% significance level. The study recommends prioritizing recurrent expenditures for essential services while enhancing capital investments in infrastructure to support economic growth. Exchange rate stability should be maintained to mitigate inflationary pressures, particularly in import-dependent sectors. Efforts to foster GDP per capita growth should include supporting private sector development and job creation. Additionally, fiscal discipline, transparency, and robust monitoring systems for public spending are crucial to ensuring efficient use of resources and controlling inflation.